Rib Fracture in Buffalo with Ruminal Cannula - Monteiro, Francisco Décio de Oliveira; Melo Alves dos Santos, Gabriela; Haick Perdigão, Hugo; Vilela Araújo, Luiz Henrique; Guimaraes Maciel e Silva, André; Sarmento Silveira, José Alcides; Dutra Duarte, Marcos; Maia Teixeira, Pedro Paulo (Acta Scientiae Veterinariae, 2020)
Background: Buffalos are very rustic animals that are adapted to adverse conditions, but the lack of adequate management can increase the susceptibility of these animals to several diseases. Rib fracture in this species is usually related to mineral deficiency and complications resulting from unappropriated management. Rib fractures in ruminants are rarely diagnosed and usually present conservative treatment; however, cases with presence of contaminated wounds require extra attention. The objective of this work was to report an atypical case of open fracture of the last rib in a buffalo with ruminal cannula, describing the case from diagnosis to surgical treatment. Case: An adult female water buffalo (Bubalus bubalis) that was well fed and receiving minerals, with implantation of a ruminal cannula, presented a lesion around the ruminal cannula, with increasing volume, exudation, and myiasis. The general parameters and behavior of the animal were apparently normal. The animal presented normal appetite and respiration and good physical condition and nutritional state, with pain reaction to the touch in the region of the lesion and their adjacencies; it presented no claudication and reluctance to remain in left lateral decubitus, and no discomfort. The clinical inspection of the cutaneous lesion showed an oblique-type fracture in the body of the last left rib, with exposed bone in the lumbar region and extremity exposed to the ruminal cannula, already presenting necrosis. The region was cleaned, removing larvae (myiasis) for better exposition of the fracture; in the following day, an osteotomy was done to remove exposed bone fragments. A trichotomy, cleaning, and debridement of the lesion and their adjacencies were done, with subsequent sedation and locoregional paralumbar anesthesia with lidocaine for resection of necrotic bone fragments. Cutaneous and muscle syntheses were not done because the region presented permanent contact with the rumen content. The post-operatory management was based on daily cleanings and bandages, with administration of antibiotics every 48 h for 20 days. The total recovery of the animal occurred within 45 days after the surgery. Discussion: Despite rib fractures in buffalos are mainly related to mineral deficiency, the case of the present study showed that these fractures are not always related to pre-existent causes. The clinical signs of the lesion were focal, because they refer to an open fracture that did not caused injuries to other structures, thus not determining an associated symptomatology. Opened rib fractures are rare, and most of them are healed by second intention without veterinary intervention. Regarding open fractures, the decontamination and debridement of a lesion and their adjacencies with removal of necrotic tissues and use of antibiotics are essential for prevention of infections. When the lesion is in a contaminated region by permanent contact with rumen content, as in this case, daily cleaning with bandages is needed for a best healing, but synthesis of tissues is not indicated because there is a possibility of contamination and formation of abscesses. Therefore, procedures that ensure the decontamination of the wound and prevention of infections with prolonged use of antibiotics are essential for a better healing of open rib fractures in regions that are subjected to constant contamination.